Association between early response of alpha-fetoprotein and treatment efficacy of systemic therapy for advanced hepatocellular carcinoma: A multicenter cohort study from China - Hou, Gang; Liu, Bo; Fan, Zhong-Qi; Li, Chao; Zhang, Jian-Ping; Guo, Yan-Hui; Zhang, Ru-Yi; Zheng, Yi; Zhu, Hong; Wang, Nan-Ya (Frontiers in Oncology, 2023)
Abstract Background: Alpha-fetoprotein (AFP) is a well-identified biomarker in hepatocellular carcinoma (HCC). However, only limited AFP-related studies have evaluated its early response to systemic therapy. This study was performed with the aim of assessing the value of early AFP response in predicting overall survival (OS) and progression-free survival (PFS) in advanced HCC patients receiving systemic therapy. Methods: This cohort study included HCC patients with baseline AFP ≥ 200 ng/ml and no prior treatment history. A > 20% decline in the serum AFP level from baseline to the first follow-up (i.e., 4 6 weeks after treatment) was defined as an early AFP response. Patient demographic information, clinical characteristics, radiological response, and survival rates were compared between patients with early AFP response and patients without early AFP response. We further utilized multivariate Cox regression to seek characteristics related to OS and PFS. Results: Among 154 patients, 69 patients (44.8%) showed an early AFP response. The disease control rate (76.8 vs. 54.1%; P = 0.003) and objective response rate (38.4 vs. 11.8%; P = 0.001) were significantly higher in patients with an early AFP response. By performing multivariate analysis, early AFP response remained the strongest risk factor for longer PFS (HR 0.546; 95% CI 0.371-0.804; P = 0.002) and longer OS (HR 0.529; 95% CI 0.335-0.834; P = 0.006). Conclusion: An early AFP response is correlated with longer overall survival and progression-free survival for advanced HCC patients receiving systemic therapy. Moreover, an early AFP response is an independent prognostic factor for longer OS and PFS. Keywords: hepatocellular carcinoma, AFP response, systemic therapy, targeted therapy, immune-based combination therapy.